2021
DOI: 10.1016/j.ejca.2021.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus plus aromatase inhibitors as maintenance therapy after first-line chemotherapy: Final results of the phase III randomised MAIN-A (MAINtenance Afinitor) trial

Abstract: Background: Despite endocrine therapy being the mainstay of treatment for hormone receptor positive (HRþ)/HER2À metastatic breast cancer, patients at risk of visceral crisis or doubt for endocrine sensitivity are still offered first-line chemotherapy. Maintenance hormonal therapy is generally offered at the discontinuation of chemotherapy. The MAINtenance Afinitor study is a randomised, phase III trial comparing maintenance everolimus combined with aromatase inhibitors (AIs) versus AI monotherapy in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In this context, type and duration of first-line chemotherapy have not been well established; however, depending on timing/magnitude of response as well as tolerability, switch to maintenance endocrine therapy (ET) is generally considered with the aim of delaying disease progression. 37 , 38 …”
Section: Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…In this context, type and duration of first-line chemotherapy have not been well established; however, depending on timing/magnitude of response as well as tolerability, switch to maintenance endocrine therapy (ET) is generally considered with the aim of delaying disease progression. 37 , 38 …”
Section: Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…To improve the efficacy of maintenance treatment, the phase III MAIN-A study compared maintenance everolimus combined with aromatase inhibitors (AI) versus AI monotherapy in patients with disease control after the first palliative chemotherapy [ 23 ]. As median PFS with 11.0 months versus 7.2 months (hazard ratio 0.71, [95% CI 0.47–1.06]) was not significantly improved and considering the substantial toxicities, the authors concluded that such a treatment strategy is not warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, everolimus combined with an aromatase inhibitor (AI) has shown promising therapeutic activity in patients suffering from breast cancer. The median PFS in the everolimus plus AI group and the AI monotherapy group was 11.0 months and 7.2 months respectively, with ORRs of 22.4% and 19.2% respectively 227 . When everolimus was combined with bevacizumab to treat patients with the RCC form of metastatic cancer, the median PFS was 13.7 months with an ORR of 35%.…”
Section: Pikk Inhibitorsmentioning
confidence: 93%